Chronology and documentary handbook of the State of Wyoming - Vexler, Robert I. (Chronologies and documentary handbooks of the States ;, 1979)
Contains a chronology of events in Wyoming from 1742 to 1977, biographical sketches of prominent citizens, and selected documents pertinent to Wyoming history.